2003
DOI: 10.1093/jxb/erg233
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of a GA 20‐oxidase in embryos from two sorghum lines with contrasting dormancy: possible participation of this gene in the hormonal control of germination

Abstract: The role of GAs in promoting seed germination is well known and experiments with seeds from different species have suggested the requirement of de novo synthesis of GAs upon imbibition for germination. There are also strong indications that the enhancement of GA synthesis is part of the mechanism through which environmental signals (i.e. light) induce germination. Since along the GA biosynthetic pathway, oxidation at C-20 carried out by GA 20-oxidases is thought to be a site of regulation, a cDNA clone encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…Additional CGs were selected based on their functional role known from other plants. As gibberellins are known to be implied in bud flushing (Or et al, 2000;Falusi and Calamassi, 2003), we included Gibberellin 20-oxidase (GA20) and Gibberellin 3-b-hydroxylase (GA3) (Perez-Flores et al, 2003;Calvo et al, 2004;Israelsson et al, 2004), which are involved in the synthesis of GA1, the active form of gibberellins in plants.…”
Section: Methodsmentioning
confidence: 99%
“…Additional CGs were selected based on their functional role known from other plants. As gibberellins are known to be implied in bud flushing (Or et al, 2000;Falusi and Calamassi, 2003), we included Gibberellin 20-oxidase (GA20) and Gibberellin 3-b-hydroxylase (GA3) (Perez-Flores et al, 2003;Calvo et al, 2004;Israelsson et al, 2004), which are involved in the synthesis of GA1, the active form of gibberellins in plants.…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptomic analysis has shown that Arabidopsis thaliana seeds imbibed at SOT activate ABA biosynthetic genes, while repressing GA biosynthetic and signaling ones (Toh et al 2008;Chiu et al 2012). ABA may be the inhibitory agent in dormant and thermodormant seeds that represses GA biosynthesis (Pérez-Flores et al 2003;Toh et al 2008) and also blocks GA signaling (Gubler et al 2002). Thus, probably in SOT-treated A. fatua PD caryopses the maintenance of relatively constant levels of ABA (Table 2) might also prevent the germination promotive action of endogenous GAs in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…ABA signalling and GA metabolism are known to play a main role during dormancy expression in immature sorghum grains (Perez-Flores et al , 2003; Rodríguez et al , 2009, 2012). Previous results with the sorghum system used here (RedlandB2, low dormancy; and IS9530, high dormancy) indicated that embryo sensitivity to ABA was related to dormancy expression in these two genotypes (Steinbach et al , 1995; Gualano et al , 2007; Rodríguez et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…GA levels, in contrast, correlated with the expression of dormancy in sorghum grains. The embryo content of active GA 4 in immature grains increased and reached a significantly higher value after a 4 d incubation period in the low dormancy line RedlandB2 as compared with the more dormant IS9530, and this increase occurred before embryo growth began (Perez-Flores et al , 2003; Rodríguez et al , 2012). It is precisely at this immature stage, before grain physiological maturity is achieved, that GA de novo synthesis contributes to germination of RedlandB2 seeds, as suggested by the results of Rodríguez et al (2012).…”
Section: Introductionmentioning
confidence: 90%